You won’t learn until you want to: medical students’ experiences of the educational nature of the clinical environment - Farzaneh Mokhtary; Elham Faghihi; Akram Sanagoo; Leila Jouybari (BMC Medical Education)
Abstract Background Acquiring basic skills and achieving professional competence depends on the quality and quantity of training in the clinical environment. Any defects or inadequacies in the education process will impact the quality and quantity of healthcare services, and ultimately, the health of individuals and society. Given the importance of this issue, the aim of this study is to elucidate the experiences of medical students regarding the educational nature of the clinical environment. Methods This qualitative study employed a conventional content analysis approach and was conducted in 2024. Data were collected through semi-structured interviews with open-ended questions regarding the experience of the “educational nature of the clinical environment.” Participants were from various fields of medical sciences and were recruited using purposive sampling. Data saturation was achieved with 22 participants. Interviews were transcribed verbatim and analyzed according to the method described by Graneheim and Lundman. All ethical considerations for human research, including informed consent and confidentiality, were observed. Results From the data analysis, four main categories and eight subcategories emerged: (a) ultimately, you are alone (passion for learning, student under pressure), (b) Instructor under the student’s microscope (instructor as a refuge for students, planning for teaching), (c) Half and incomplete clinical environment (lack of resources, unequal learning opportunities), (d) Communication, key to learning in practice (better communication: more learning, accompanying the patient in learning). Conclusions The findings of this qualitative study provide significant insights into medical students’ experiences in the clinical setting, highlighting the need for a transformative approach to clinical education policies and practices. Students’ narratives emphasize the importance of creating an environment that encourages autonomy and active learning and addresses the pressures and challenges they face, such as inadequate resources, high stress levels, and unequal learning opportunities. To improve the educational experience, clinical education policies should prioritize equitable access to learning resources, promote a culture of respect, and collaboration among all healthcare professionals. By addressing these critical areas, clinical education can better prepare future healthcare professionals to navigate the complexities of patient care.